Agricultural technology adoption, commercialization and smallholder rice farmers' welfare in rural Nigeria - Bola Amoke Awotide; Aziz A. Karimov; Aliou Diagne (Agricultural and Food Economics, 2016)
This study assessed the determinants of intensity of adoption of Improved Rice Varieties (IRVs) and the effect of market participation on farmers' welfare in Nigeria using the Tobit and Heckman two-stage models, respectively. The sample consists of crosssectional data of 600 rice farmers selected randomly from three notable rice producing States in Nigeria. The variables that positively and significantly influenced the intensity of IRVs adoption include income from rice production, membership of a farmers' organization, and the distance to the nearest sources of seed, cost of seed, yield and level of training. Gender of household head, access to improved seed, years of formal education, and average rice yield were those variables that are positive and statistically significant in increasing the probability that a farmer would participate in the market. The result further suggests that any increase in the farmers' welfare is conditional on the probability of the farmer participating in the rice output markets. In addition, higher yield, income from rice production, gender of household head, and years of formal education are the variables that are positive and statistically significant in determining households' welfare. Therefore, it is recommended that formation of associations among the rural farmers should be encouraged. Access to seed and information about the IRVs are also essential to increase the intensity of its adoption. Programmes to improve contact with extension agents, increased access to credit, raising educational background and increasing the area devoted to cultivating IRVs are the factors to be promoted in order to increase market participation and hence improve the welfare of rural households.
Keywords: Q13; Q16; O13; 330; Rice; Adoption; Commercialization; Farming; Welfare; Nigeria